2021
DOI: 10.3390/jcm10225287
|View full text |Cite
|
Sign up to set email alerts
|

Fragility Index and Fragility Quotient in Randomized Controlled Trials on Corticosteroids in ARDS Due to COVID-19 and Non-COVID-19 Etiology

Abstract: Background: The effectiveness of corticosteroids in acute respiratory distress syndrome (ARDS) and COVID-19 still remains uncertain. Since ARDS is due to a hyperinflammatory response to a direct injury, we decided to perform a meta-analysis and an evaluation of robustness of randomised clinical trials (RCTs) investigating the impact of corticosteroids on mortality in ARDS in both COVID-19 and non-COVID-19 patients. We conducted a systematic search of the literature from inception up to 30 October 2020, using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…The FI has been reported for a number of medical and surgical RCTs, including cerebrovascular surgery, 2 critical care, 4 , 41 nephrology, 42 hand surgery, 5 and cardiovascular trials. 43 To the authors’ knowledge, this is the first study to evaluate the FI for interventional radiology trials.…”
Section: Discussionmentioning
confidence: 99%
“…The FI has been reported for a number of medical and surgical RCTs, including cerebrovascular surgery, 2 critical care, 4 , 41 nephrology, 42 hand surgery, 5 and cardiovascular trials. 43 To the authors’ knowledge, this is the first study to evaluate the FI for interventional radiology trials.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical fragility is poorly understood, with no consensus on cut-offs to determine whether a study is significantly fragile or robust. However, multiple studies have shown high fragility in the medical literature (3,7,8).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that, on average, half a percent of study participants would need to have their outcomes changed from an event to a non-event for the trial results to turn from statistically significant to statistically not significant. In other words, the FQ provides a measure of how sensitive trial results are to changes in a small number of participants [37,38]. A low FQ value means that a trial result is relatively robust and not overly sensitive to small changes in the number of outcomes, and vice versa.…”
Section: Fragility Indexmentioning
confidence: 99%